2022
DOI: 10.1111/pbi.13794
|View full text |Cite
|
Sign up to set email alerts
|

OsCOMT, encoding a caffeic acid O‐methyltransferase in melatonin biosynthesis, increases rice grain yield through dual regulation of leaf senescence and vascular development

Abstract: Summary Melatonin, a natural phytohormone in plants, plays multiple critical roles in plant growth and stress responses. Although melatonin biosynthesis‐related genes have been suggested to possess diverse biological functions, their roles and functional mechanisms in regulating rice grain yield remain largely unexplored. Here, we uncovered the roles of a caffeic acid O‐methyltransferase (OsCOMT) gene in mediating rice grain yield through dual regulation of leaf senescence and vascular development. In vitro an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 74 publications
0
31
0
Order By: Relevance
“…Through the dual regulation of leaf senescence and vascular development, a recent study discovered the involvement of a caffeic acid O-methyltransferase ( OsCOMT ) gene in modulating rice grain yield. 127 The results revealed that OsCOMT is involved in the production of MET. 127 According to transgenic assays, OsCOMT dramatically slowed down the senescence of leaves at the grain-filling stage by preventing the breakdown of Chl and chloroplast, which boosted the effectiveness of photosynthesis.…”
Section: Melatonin-mediated Genetic Engineering In Improving Temperat...mentioning
confidence: 95%
See 1 more Smart Citation
“…Through the dual regulation of leaf senescence and vascular development, a recent study discovered the involvement of a caffeic acid O-methyltransferase ( OsCOMT ) gene in modulating rice grain yield. 127 The results revealed that OsCOMT is involved in the production of MET. 127 According to transgenic assays, OsCOMT dramatically slowed down the senescence of leaves at the grain-filling stage by preventing the breakdown of Chl and chloroplast, which boosted the effectiveness of photosynthesis.…”
Section: Melatonin-mediated Genetic Engineering In Improving Temperat...mentioning
confidence: 95%
“… 127 The results revealed that OsCOMT is involved in the production of MET. 127 According to transgenic assays, OsCOMT dramatically slowed down the senescence of leaves at the grain-filling stage by preventing the breakdown of Chl and chloroplast, which boosted the effectiveness of photosynthesis. Briefly, MET-mediated leaf senescence and vascular development offer a potential method for genetically enhancing rice grain output.…”
Section: Melatonin-mediated Genetic Engineering In Improving Temperat...mentioning
confidence: 95%
“…Although ascorbic acid and 3-OHM are antioxidants, they have different biological functions in flowering. Further studies of melatonin and its metabolites (e.g., 2-OHM and 3-OHM) will shed light on their biological functions and interactions in plants [ 7 , 25 , 46 , 51 , 52 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Knock down of OsTAL reduced the number and area of stem lvbs, and significantly decreased GN and grain yield ( Yang et al, 2015 ). The OsCOMT ( caffeic acid O-methyl transferase ) gene, which encodes the rate-limiting enzyme in melatonin biosynthesis, positively regulates GN and grain yield through promoting vascular development and delaying leaf senescence ( Huangfu et al, 2022 ). Overexpression of OsCOMT can significantly improve the vascular bundle size and number, and increase GN ( Huangfu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The OsCOMT ( caffeic acid O-methyl transferase ) gene, which encodes the rate-limiting enzyme in melatonin biosynthesis, positively regulates GN and grain yield through promoting vascular development and delaying leaf senescence ( Huangfu et al, 2022 ). Overexpression of OsCOMT can significantly improve the vascular bundle size and number, and increase GN ( Huangfu et al, 2022 ). It is suggested that the improved vascular system (flow) may promote the translocation of photoassimilates from source to sink organs ( Li et al, 2018b ).…”
Section: Introductionmentioning
confidence: 99%